AN INTEGRATIVE MODEL OF COMPETENCE, COMMITMENT, AND PERFORMANCE IN ACHIEVING ORGANISATIONAL EFFECTIVENESS - Apris Beniawan; Lijan Poltak Sinambela; Tri Waluyo (International Journal of Social Science, 2025)
This study explores an integrative model of competence, commitment, and performance in achieving organizational effectiveness. Modern organizations face increasingly complex challenges that require strategic human resource approaches. Competence encompasses the knowledge, skills, and attitudes that enable individuals to perform tasks effectively. Organizational commitment reflects employees’ emotional and psychological attachment to the organization’s values and goals. Performance is the tangible outcome of accumulated competence and commitment, manifested in productivity, work quality, and contributions to strategic objectives. The research was conducted at Barantin using a quantitative approach with Structural Equation Modeling (SEM) via SmartPLS. The sample consisted of 160 purposively selected respondents. The results indicate that employee performance has the most dominant influence on organizational effectiveness (original sample value 0.559; T-statistic 6.677), followed by organizational commitment (0.264; T-statistic 3.530), and work competence (0.161; T-statistic 2.887). All three variables show statistically significant effects on organizational effectiveness. This integrative model confirms that enhancing organizational effectiveness cannot rely on improving a single factor alone. Instead, it requires the synergy of competence, commitment, and performance. These findings support previous literature and offer a practical framework for HR policymakers to design sustainable and adaptive managerial interventions in response to evolving workplace dynamics.